If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4w + 17 = 93 Reorder the terms: 17 + 4w = 93 Solving 17 + 4w = 93 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 4w = 93 + -17 Combine like terms: 17 + -17 = 0 0 + 4w = 93 + -17 4w = 93 + -17 Combine like terms: 93 + -17 = 76 4w = 76 Divide each side by '4'. w = 19 Simplifying w = 19
| -2=5x-5 | | 16a+16b+2c+2c-5b-4a= | | 8=9x+3 | | 32-8a=52-6a+2 | | -3=5x-5 | | (7x+3)-2=22 | | 6k+24=3k-12 | | 12v^7w^9+16v^4w^5x^8=0 | | 11+5(k+1)=3k-(6k-6) | | F(x)=lhx+2 | | 4.2x-2.1=1.68-5.4x | | -26+3x=-36+6x | | 5-3x=7x+5 | | 102=5w+17 | | -9(x-4)=-3x+42 | | 12-2x=2x+8 | | X=8-3(-3) | | A=10x+y+2 | | 21+3x=56 | | -9x-4y=-4 | | -x=-3+2x | | 210p=1890 | | 3x-5=12+3x | | 6n+10=-4n+50 | | 8*n=32 | | 16x^2-27e=0 | | 10=6x+3 | | 9x+11=6x+-9+3 | | 3x-18=12+7x | | 4x-4x+5=12 | | 4+5(x-2)=6+7(x-2) | | (10-2x)(8-2x)(x)=f(x) |